Dynamic Changes of Immunoreactive CD34, CD117, and CD41 Hematopoietic Stem Cells in Human Placentas of Different Gestational Ages - Sanja Jovicic; Ivan R. Nikolic; Ljiljana Amidžić; Vesna Ljubojevic; Maja Barudzija; Ranko Skrbic (Journal of Developmental Biology)
Background: The process of prenatal hematopoiesis occurs in various anatomical locations, including the placenta. The placenta is not merely a temporary hematopoietic reservoir, but it is one of the key sites for the synthesis of hematopoietic stem cells (HSCs). This study aimed to investigate the presence, distribution, and immunoprofiles of HSCs in the human placenta during different gestational periods. Materials and Methods: Placental samples of different gestational ages (first, second, and third trimesters) were analyzed using classical hematoxylin and eosin staining and immunohistochemical staining for CD34, CD117, and CD41 markers, with HSC quantification through numerical areal density (NA). Results: Highly immunoreactive CD34 HSCs were present in placentas throughout gestation, while highly immunoreactive CD117 and CD41 HSCs were observed during the first two trimesters. In the first trimester, HSCs were found within the lumen of blood vessels and as individual cells in the mesenchyme of chorionic villi. With advancing gestation, the number of HSCs in the mesenchyme of chorionic villi increased. Conclusions: Immunoreactive CD34, CD117, and CD41 cells are present in significant proportions in various parts of the placenta throughout gestation, indicating that the placenta provides a substantial proportion of HSCs for hematopoiesis.